The role of Islamic education teachers in promoting the values of faith among middle school students in the judiciary in Al-dour and Al-alam in salah Al-Din Governorate - khudhur , Sabah (Islamic Sciences Journal, 2023)
The study sought to identify the role of Islamic education teachers in promotingthe values of faith among middle.school students in the Durr and Science judgements. The researcher used the descriptive curriculum in his study because it is the appropriate curriculum for ths stud.The study community is represented by middleschool teachersn the Dor and Science judgement. The number of schools for the 2021/2022 academic year was(45)including(22) secondary schools for boys, (17) secondary schools for girls and (6) mixed schools. To achieve the purpose of the study and to indicate its objective, the researcher prepared a sample of six areas derived from the pillars of faith. He then confirmed the validity of the study and the distribution of(80) schools and (8)schools The study, with (40) male teachers and (40) female teachers,the results of the study showed that the role of Islamic education teachers in promoting the values of faith among middle school students was high. The results of the study also showed that the appreciation of Islamic education teachers for the fields of faith value(promoting the values of faith in God, strengthening the values of faith in angels, promoting the values of faith in the apostles, strengthening the values of faith in divine books, promoting the values of faith in fate, its good and its evil, and the instrument as a whole) were high as well. The researcher recommended paying attention to the values of faith in educational and educational programs,he also recommended the inclusion of areas of religious values in the Ministry of Education's curricula, stressing the need to continuously evaluate the areas of religious values that students have acquired, and to conduct more studies at different stages of study to identify the effects of religious values on students' behavior and its reflection on society.